X-ray beam test of fabricated photo-diodes for Pohang-Accelerator-Laboratory X-ray free-electron laser - Lee, S. C.; Hyun, H. J.; Baek, J. M.; Hwang, S. M.; Jang, H.; Kim, J. Y.; Kim, S. H.; Park, H. (Frontiers in Physics, 2024)
The Pohang-Accelerator-Laboratory X-ray free-electron laser (PAL-XFEL) emits intense, ultra-short X-ray pulses, enabling studies on ultra-small and -fast dynamics in various fields. We designed and fabricated silicon p-intrinsic-n photo-diodes (PDs) to detect strong X-ray pulses. Four types of PDs were fabricated with different metal shapes on the P- and N-sides. The fabrication process was split into two parts, based on the thickness of the Al metal and anti-reflective coating (ARC) layers, to evaluate the fabrication process feasibility and the detection performance. A beam test was performed with X-ray pulses at the soft X-ray beamline of the PAL-XFEL using the proposed PDs and a commercial PD. The test was designed to evaluate the effects of the metal and ARC layers and compare the detection efficiency depending on the X-ray entrance side and signal readout side. The waveforms were saved during the test and integrated to obtain the charges. Thereafter, they were analyzed and normalized, and compared. This paper presents the preparation, setup, and procedure of the beam test, and the test results are described.